Motivational Interviewing for Adolescent Substance Use: A Review of the Literature - Barnett, Elizabeth (2012)
Motivational Interviewing (MI) is a widely-used approach for addressing adolescent substance use. Recent meta-analytic findings show small but consistent effect sizes. However, differences in intervention format and intervention design, as well as possible mediators of change, have never been reviewed. This review of the literature summarizes the most up-to-date MI interventions with adolescents, looks at differences between intervention format and design, and discusses possible theory-based mechanisms of change. Of the 39 studies included in this review, 67% reported statistically significant improved substance use outcomes. Chi square results show no significant difference between interventions using feedback or not, or interventions combined with other treatment versus MI alone. The need for systematic investigation in theory-based mechanisms of change is presented.